2019
DOI: 10.1001/jamanetworkopen.2019.11528
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perceptions of the Use of Social Media for Recruitment of Patients in Cancer Clinical Trials

Abstract: Key PointsQuestionWhat are physicians’ attitudes toward and perceptions of using social media to recruit participants for cancer clinical trials?FindingsIn this qualitative study of 44 physicians from academic and community practices, physicians cited increased trial awareness and visibility as advantages of social media. Commonly cited disadvantages were increased administrative burden and risk of misinformation.MeaningThis study’s findings suggest that physicians are aware of the benefits of social media as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Eligible participants included investigators of study protocols from January 1, 2013, to October 14, 2019. The survey instrument was constructed on the basis of prior qualitative work, 3 reviewed by methodologists and clinical experts, and pilot tested (eAppendix 1 in the Supplement ). The study followed the American Association of Public Opinion Research ( AAPOR ) reporting guideline 4 and was approved by the City of Hope institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Eligible participants included investigators of study protocols from January 1, 2013, to October 14, 2019. The survey instrument was constructed on the basis of prior qualitative work, 3 reviewed by methodologists and clinical experts, and pilot tested (eAppendix 1 in the Supplement ). The study followed the American Association of Public Opinion Research ( AAPOR ) reporting guideline 4 and was approved by the City of Hope institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…A recent qualitative study including 44 physicians who used Social media for their research recruitment, observed that awareness and visibility of social media had increased among physicians; however, the top cited disadvantages of Social media use were administrative burden and risk of misinformation, as well as lack of evidence that Social media was a benefit to the medical professional. 18 During an interview study, physicians reported a need for more training on the use of social media using evidence-based approaches, facilitators for professional social media use, a need to address the lack of time, as well as lack of evidence of benefit. 19 Some organizations are addressing this need with opportunities for certification in Social media and healthcare with provision for in depth training on these topics, including privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous challenges and ethical barriers, social media channels are also increasingly employed for establishing physician-patient communication, receiving their comments, and recruiting them in clinical research studies [14][15][16].…”
Section: Social Media Benefits For Scholarsmentioning
confidence: 99%